Filosofi Teras: Filsafat Kuno untuk Mental Tangguh Masa Kini - Limbong, Ayu Miranda; Asbari, Masduki (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to review the book as an effort to explore and understand the scientific narrative of the book